PERUSAHAAN ROKOK CV. ULUNG BOJONEGORO TAHUN 1993-2015 - Hapsari, Olyvia Dian; Wisnu, Wisnu (AVATARA e-Journal Pendidikan Sejarah, 2021)
CV. Ulung as a cigarette company in Bojonegoro is very interested to reseached, because of its existence still holding till now. Although there are so many merk of cigarette which grew up. And its also has a problem from goverment ban because of its raw material is very dangerous. All of them are regulated in Government Regulation of the Republic of Indonesia Number 81 of 1999 as a continuation of Law number 23 of 1992 article 44 which regulates the safety of cigarette products for health. CV. Ulung Cigarette Company produces two types of cigarettes, there are paper kretek cigarettes and kelobot cigarettes under the brand name Cap Oeloeng. Thats why, the survival of this company, interested the author to found more information about the background of the CV.Ulung as a cigarette company from its build and how the strategy to keep exist with the smoker from 1993 till 2015. So we get the formulation problems that are 1. How do the dynamics of CV. Ulung as a cigarette company from 1993-2015 ? 2. What are the factors that support and inhibit the growth and development of CV. Ulung as a cigarette company ? 3. How is the strategy developed that the CV. Ulung as a cigarette company can survive? The problems of this research will be examined using historical research methods and are divided into four stages. There are heuristics (source collection), criticism (verification), interpretation (interpretation) and historiography (writing history). The results obtained during the study indicate that the survival of the CV. Ulung as a cigarette company due to the efforts in carrying out the strategy by improving the quality of its products, establishing good communication with the Indonesian Kretek Community and the existence of consumers who are still loyal to consuming Cap Oeloeng cigarettes. Most of the consumers are from old age people who used to consume Cap Oeloeng cigarettes when they were young. In another side, people from the lower economic class also very loyal to consume cigarette from Cap Oeloeng. Keywords: Cigarettes, CV Ulung, Oeloeng Cigarettes